Effects of submarine groundwater on nutrient concentration and primary production in a deep bay of the Japan Sea - M. Dong; X. Guo; T. Matsuura; T. Tebakari; J. Zhang (Biogeosciences)
We constructed a coupled physical–ecosystem model with a tracking module to evaluate the influence of submarine groundwater discharge (SGD) and river water on nutrient distribution and phytoplankton growth in Toyama Bay, a deep bay in the Japan Sea (Sea of Japan). The tracking technique allows us to distinguish SGD- and river-derived nutrients in the bay and evaluate their contributions to the nutrient inventory and phytoplankton growth. Horizontally, SGD-derived nutrients were primarily distributed within a narrow band from the coastline (<3 km), and vertically, they were abundant in the middle and bottom layers (>5 m depth). Because of the buoyancy of SGD, SGD-derived nutrients were transported upward to the surface layer and used by the phytoplankton for growth. The contribution of SGD-derived nutrients to phytoplankton growth within a narrow band from the coastline is highest from June to August, exceeding 10 %, with an annual average of 4 %. On the other hand, river water exerted a greater effect on phytoplankton growth than SGD did, on both the spatial range and the amount of phytoplankton biomass. Due to the different distributions of river- and SGD-derived nutrients, their proportions used by phytoplankton differed from coastal to offshore areas. These findings enhance our understanding of the coastal ecosystems affected by land water.